HUBUNGAN KECANDUAN GADGET TERHADAP POLA TIDUR SISWA MI MIFTAHUL ULUM DESA SAPON KECAMATAN KESAMBEN KABUPATEN JOMBANG - Nur Haqiqi, M. Hafidz; Eko Kurniawan, Vendi; Melliya Sari, Gevi; Febrianto, Kiki; Shomad, Miftahus (PRIMA WIYATA HEALTH, 2024)
Continuous use of gadgets can affect children's daily activities. Gadget addiction also makes children vulnerable to disturbed sleep patterns. Purpose of this study to determine the relationship between gadget addiction and sleep patterns of MI Miftahul Ulum students in Sapon Village, Kesamben District, Jombang Regency. Descriptive correlation study with a cross-sectional approach in MI Miftahul Ulum students of Sapon Village, Kesamben District, Jombang Regency. 38 samples were obtained using purposive sampling. Data collection through SDCC questionnaire sheet and smartphone addiction questionnaire. Data analysis with Spearman Rank test. Results showed that most of respondents experienced moderate gadget addiction, 26 respondents (68.4%). Almost all respondents had poor sleep patterns of 20 respondents (52.6%). According to spearman rank test, the α value is 0.000 (a <0.05), then H1 can be accepted and H0 cannot be accepted, showed that there is a relationship between gadget addiction and sleep patterns of MI Miftahul Ulum students in Sapon Village, Kesamben District, Jombang Regency. Gadget addiction has a significant impact on student sleep patterns. Students are expected to use gadgets as needed by understanding the functions, benefits and impacts of gadgets. Preventive measures, education and supervision are needed.